(untitled) (Mustansiria Dental Journal, 2018)
The aim of this descriptive analytic retrospective study was to evaluate the etiology, clinical features and treatment data of patients with zygomatic complex fractures at our program during a 5-year period. From March 1998 until February 2003. 69 patients presented with zygomatic complex fractures were treated by the department of Oral & Maxillofacial Surgery at Baghdad College of Dentistry and private clinic in Iraq. Patient’s information was collected using a specifically designed form. The patient age ranged from 5-68 years with a mean age of 30.5 years, 51 of them were males and 18 were females. Road traffic accidents (43.5%) was the major cause for fractures (P<0.05). regarding clinical features subconjunctival ecchymosis (61%) and circumorbital ecchymosis (53.6%) were most common observed. The Gillies approach (26%) was the commonest method of reduction. This study has shown that road traffic accidents are responsible for most zygomatic complex fractures in our environment. It also showed a low utilization of technological advances in the imaging and treatment of these fractures.